Algorithms, blockchain & cryptocurrency : implications for the future of the workplace - Brown, Gavin; Whittle, Richard (The future of work, 2020)
The convergence of Algorithms, Blockchain and Cryptocurrency has the potential to fundamentally disrupt the current world of work. This book investigates the effects of this on the worker, the organisation and the economy, by considering a future where the traditional power relationships between workers and firms no longer apply. Using the term "Bitwork" to define this future world of work, the book proposes the idea of the Bitworker who is highly flexible, holds multiple roles, and has multiple incomes. Chapters consider the potential winners and losers of this technological pivot by exploring implications such as: the expanding array of currencies; training and education; retirement and loyalty; profit and power within organizations; economic policy. The books comprehensive recommendations on how workers, organisations and nation states will need to adapt to prosper in this new world, provide a useful survival guide for researchers, practitioners and policy makers working on behavioural economics, economic policy and the future of work.